2015
DOI: 10.1002/hep.28297
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis C virus–associated mixed cryoglobulinemia with direct‐acting antiviral agents

Abstract: Background Hepatitis C virus (HCV) is the most common cause of mixed cryoglobulinemia syndrome (MCS). The efficacy and safety of all-oral directly-acting antiviral (DAA) therapy in HCV-associated MCS (HCV-MCS) is largely unknown. Methods Case series of patients with HCV-MCS who were treated with sofosbuvir-based regimens and historical controls treated with pegylated interferon and ribavirin in a single healthcare network. HCV-MCS was defined by circulating cryoglobulin associated with systemic vasculitis sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
201
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(212 citation statements)
references
References 33 publications
(56 reference statements)
7
201
1
3
Order By: Relevance
“…Sustained virological response is the main goal in these patients since clinical remission of vasculitis is closely associated with viral clearance 8 . Few studies have reported promising results on the effectiveness and tolerance of direct acting antiviral drugs (DAA), either in association with interferon (IFN) or using IFN-free regimens [8][9][10][11] . The aim of the present study was to evaluate effectiveness and tolerance of an all oral IFN-and ribavirin-free regimen with sofosbuvir plus daclatasvir in patients with cryoglobulinemia vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…Sustained virological response is the main goal in these patients since clinical remission of vasculitis is closely associated with viral clearance 8 . Few studies have reported promising results on the effectiveness and tolerance of direct acting antiviral drugs (DAA), either in association with interferon (IFN) or using IFN-free regimens [8][9][10][11] . The aim of the present study was to evaluate effectiveness and tolerance of an all oral IFN-and ribavirin-free regimen with sofosbuvir plus daclatasvir in patients with cryoglobulinemia vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…For at least some patients with severe cryoglobulinemia achievement of SVR may be insuffi cient to complete mitigate its manifestations, and additional support with rituximab and/or plasmapheresis may still be required. However, this report and others indicate that inferior SVR rates in HCV patients with cryoglobulinemia have been overcome with DAA therapy ( 8,9 ), and that clinical improvement, although not inevitable, typically follows. Th e enhanced effi cacy of DAA has simplifi ed management of this important manifestation of HCV infection.…”
mentioning
confidence: 66%
“…patients with decompensated cirrhosis, renal impairment, HIV/HCV or HBV/HCV co-infections and those who develop recurrent HCV infection following liver transplantation) and pre-treatment assessment of patient's understanding of the goals of therapy as well as the need for adherence and follow up. Studies have shown that reduction in severity of disease and eventual cure for HCV contribute to dramatic reduction in all-cause mortality (including hepatic decompensation events, hepatocellular carcinoma and liver-related mortality) and improve quality of life [61][62][63][64][65][66] . Dhawan documented various drug regimens for the treatment of hepatitis C [67] .…”
Section: Discussionmentioning
confidence: 99%